Limbah Cangkang Telur dan Sekam Padi Sebagai Filler Dengan Batu Pecah Madura Sebagai Aggregat Pada Campuran ACWC - Ahmad Fatoni; Dedy Asmaroni; Khairul Anam; Aldi Setiawan (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
Filler is one of the additives in hot asphalt mix, and its cost is relatively high. Therefore, there is a need for innovation to utilize local materials that are more economical. In this study, rice husk ash and eggshell waste are utilized as fillers, and local crushed stone is used as the aggregate, considering the potential of local materials and their cost-effectiveness. These waste materials have been underutilized and have had environmental impacts. The research aims to investigate the influence of using rice husk ash and eggshell waste as fillers on the Marshall characteristics by employing the Marshall Test method to determine values such as stability, flow, VIM (voids in mix), VMA (voids in mineral aggregate), VFB (voids filled with bitumen), and Marshall Quotient (MQ). Fillers, in the amounts of 1%, 2%, 3%, 4%, and 5% of the total weight of the mix, will be used, with each using eggshell waste and rice husk ash in equal proportions of 50% of the total filler requirement, along with the use of local aggregate. The research findings indicate that using 4% and 5% eggshell waste and rice husk ash fillers produces good stability values, meeting the General Specifications for Road Works 2018 Division 6. However, the addition of 1%, 2%, and 3% of these fillers leads to a decrease in stability values. Furthermore, an increase in the percentage of eggshell waste and rice husk ash fillers by 2%, 3%, 45 and 5% contributes to a reduction in flow values or workability